Le virus du racisme : ses formations discursives et son contrediscours dans la littérature issue de l’immigration postcoloniale - Véronic Algeri (MediAzioni)
As a virus, which can only reproduce itself by parasitizing a cell before multiplying within an organism and spreading while retaining its elusive nature and its multiform character, racism transmits from one person to another, it infiltrates the social body and can be encouraged or countered. This analogy is explored to consider the circulation of racism, its dissemination from one community to another, its shift from one locutor to another, each one producing its own symptomatologic framework: from institutional formulas, with their watchwords, to expressions of ordinary racism, with its little phrases. All these forms of discourse contribute to the creation of urban and socio-identitarian cleavages and produce social distancing. When it reaches its targets, by replicating itself, the racism virus undergoes mutations. Locutors who are the victims of stigmatising attacks seize on racist formulas and transform them into polemical objects by means of various metadiscursive devices to finally produce a counter-discourse. In the corpus we are presenting, made up of a sample of contemporary narrative texts by authors of postcolonial immigrant background, we observe, by means of discourse analysis, that racist formulas are identified and resignified within a polyphonic context.